2011
DOI: 10.1021/jp201494p
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Surface Acidity of Silica-Supported Dodecatungstosilicic Acid in Relation to the Loading Amount

Abstract: Changes in surface acidity of H4SiW12O40/SiO2 in relation to the loading amount were investigated by using temperature-programmed desorption (TPD) of benzonitrile (BN), BN infrared (BN-IR) spectroscopy, and test reactions, including skeletal isomerization of n-butane and double-bond shift of 1-butene. From BN-TPD profiles and BN-IR spectra, H4SiW12O40/SiO2 had medium strength Brønsted (Mid-B site) and strong Brønsted acid sites (Strong-B site) on its outermost surface, whereas there was no evidence for Lewis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 61 publications
(86 reference statements)
2
9
0
Order By: Relevance
“…700°C for HSiW@SBA-15. All these results are in agreement with the data reported in the literature [43,44,47]. A more quantitative comparison of the data gives 1.5 mmol NH 3 desorbed per g of H 3 PW 12 O 40 for the bulk HPA, 0.3 mmol NH 3 desorbed per g of SBA-15 and around 2 mmol NH 3 desorbed per g for the SBA-15 supported and encapsulated HPA (Tab.…”
Section: Study Of the Acidity Of The Catalysts By Adsorptiondesorptiosupporting
confidence: 91%
See 1 more Smart Citation
“…700°C for HSiW@SBA-15. All these results are in agreement with the data reported in the literature [43,44,47]. A more quantitative comparison of the data gives 1.5 mmol NH 3 desorbed per g of H 3 PW 12 O 40 for the bulk HPA, 0.3 mmol NH 3 desorbed per g of SBA-15 and around 2 mmol NH 3 desorbed per g for the SBA-15 supported and encapsulated HPA (Tab.…”
Section: Study Of the Acidity Of The Catalysts By Adsorptiondesorptiosupporting
confidence: 91%
“…Ammonia is often used as a probe molecule for the determination of the acidity of the solids, for example by studying its adsorption by microcalorimetry or its desorption from a catalyst previously saturated with it (TPD) [43][44][45]. We used these two methods in order to compare the acidity of the impregnated and encapsulated catalysts as the catalytic reactivity had shown a difference in the behavior of the HSiW@SBA-15 system compared to the three other ones.…”
Section: Study Of the Acidity Of The Catalysts By Adsorptiondesorptiomentioning
confidence: 99%
“…Acid strengths classification of these developed catalysts were tabulated in Table 2 [14][15][16]. As c , " " increasing acid loadings [17,18]. Thought similar trend was reported [19], we concluded that partial agglomeration of HPW crystal on external surfaces at high HPW loading might have occurred.…”
Section: Characterizations Of Hpw Post Impregnated Sba-15supporting
confidence: 63%
“…With silica-supported HPAs at low and medium HPA loadings, both polar and nonpolar substrates typically react via the surface-type catalysis, showing similar dependencies between catalyst activity and HPA loading—the activity, expressed as substrate conversion or reaction rate per total weight of HPA/SiO 2 catalyst, increases with HPA loading at a constant HPA/SiO 2 catalyst weight, reaching a plateau at 25–40% loading, or passes a maximum. 26 , 34 , 38 This is the result of a trade-off between the density of surface proton sites and their strength at varying HPA loading. The proton site density (per total catalyst weight) passes a maximum at a medium HPA loading due to the sharp decrease in catalyst surface area to less than 10 m 2 g –1 for bulk HPA.…”
Section: Resultsmentioning
confidence: 99%
“…Using the TPD of benzonitrile, which interacts only with the surface acid sites in HPA, the amount of strong surface Brønsted sites in HSiW/SiO 2 has been found to pass a maximum at a HSiW loading of ∼50%. 34 …”
Section: Resultsmentioning
confidence: 99%